The Role of Productive Zakat in Improving the Welfare of Mustahik in Indonesia - Gofur, Ahmad Abdul; Kasri, Rahmatina Awaliah (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
The distribution of consumptive zakat often yields only short-term benefits, failing to provide a sustainable solution for poverty alleviation efforts, including in Indonesia. In response, the concept of productive zakat has emerged, aiming to transform mustahik (zakat recipients) into muzakki (zakat payers) through capital support or business facilitation. However, limited research has explored the role of productive zakat in enhancing the welfare of mustahik, particularly at the national level. This study aims to identify the factors affecting in increasing in income among mustahik receiving productive zakat in Indonesia. Utilizing secondary data from BAZNAS covering 1,631 mustahik, this research employs a logistic regression model to address the research question. The dependent variable is the increase in mustahik income, while the independent variables include the amount of zakat assistance, frequency of zakat distribution, regional grouping, and the provision of training and mentoring. Control variables include the number of family members, gender, age, education, and prior business ownership. The results indicate that the amount of zakat assistance, the provision of training and mentoring, being female, being of productive age, and having owned a business prior to the zakat intervention have a positive effect on income growth among mustahik. In contrast, the frequency of zakat provision, regional group, number of family members, and education level do not have a significant effect on mustahik income. Based on these findings, zakat institutions are encouraged to increase the allocation of productive zakat to support new or existing small enterprises, accompanied by training and mentoring programs tailored to the demographic characteristics of the mustahik. This approach provides insight to enhance the effectiveness of productive zakat programs in improving the welfare of recipients as well as contribute to the academic literature on the role of zakat in poverty alleviation.